Mengelola Keuangan Dengan Bijak Menggunakan Aplikasi Excel - Ferdinando Solissa; Putu Anggreyani Widya Astuty; Margaretha Turot; Ignatz Novrian Fayliencent; Iyonna J Salakay; Irwan Soulisa; David Gilbert Matatula; Natasya Virgina Leuwol (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The Community Service (PKM) activity carried out by the Accounting Study Program of Victory University Sorong is the third activity at the request of the Principal of SMK Negeri 1 Sorong Regency in the implementation of the Tridharma of Higher Education, specifically to introduce and train the use of Microsoft Excel applications to students of SMK Negeri 1 Sorong Regency. The results of this PKM activity A total of 15 participants were selected by the school based on the number of computers available in the school lab During the activity, participants showed high participation and enthusiasm, both in theory and practice sessions. This activity also received full support from the school, including the principal and accompanying teachers, who helped ensure the smooth implementation. In general, this PKM activity ran smoothly. This was achieved thanks to the support of the school and the lecturers of Victory University Sorong. This activity also involved 3rd semester accounting students. The purpose of this activity is to implement knowledge to students regarding excel formulas used for mathematical calculations (SUM, AVERAGE), logic (IF), data searches (VLOOKUP), text (LEFT, RIGHT, MID, CONCATENATE), or statistics (COUNT, MAX, MIN), helping to create excel templates that are ready to be used in practicing making journals, ledgers and financial reports that are automatically filled in.